1999
DOI: 10.1002/(sici)1099-0690(199903)1999:3<691::aid-ejoc691>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 2,3,5-Tri-O-benzyl-4-thio-L-arabino-furanosides and the Corresponding 4′-Thionucleoside Analogues

Abstract: 1‐O‐Acetyl‐2,3,5‐tri‐O‐benzyl‐4‐thio‐L‐arabino‐furanose (9) has been prepared from D‐xylose via the 1,4‐dithio‐L‐arabino‐furanoside 8. The crucial step of the reaction, i.e. the intramolecular cyclization of the open‐chain dithioacetal 5, has been achieved in a yield of 90% by applying tetrabutylammonium iodide as promoter. Reaction of 9 with bis(trimethylsilyl)uracil or ‐thymine led to the benzyl derivatives 12 and 13 from which the deprotected 4′‐thionucleoside analogues 14 and 15 have been prepared by deben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…Crude 22 (1.73 mmol) was dissolved in acetic anhydride (15 mL), and the mixture was stirred at 100 °C for 3 h. The reaction mixture was concentrated in vacuo, and column chromatography (pentane/EtOAc, 90:10 to 80:20) yielded the title compound (0.88 mmol, 0.42 g, 51% over two steps): 1 H NMR (400 MHz, CDCl 3 ) δ 7.41–7.23 (m, 15H), 6.11 (d, J = 4.0 Hz, 1H), 6.02 (d, J = 3.0 Hz, 1H), 4.86–4.50 (m, 6H), 4.30 (dd, J = 5.2, 3.1 Hz, 1H), 4.27–4.12 (m, 2H), 4.07 (dd, J = 6.5, 5.2 Hz, 1H), 3.81 (q, J = 6.4 Hz, 1H), 3.77–3.68 (m, 2H), 3.59–3.39 (m, 3H); 13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ 138.4, 138.0, 137.6, 128.6, 128.6, 128.5, 128.5, 128.1, 128.1, 128.0, 128.0, 127.9, 127.9, 127.8, 127.8, 88.9, 86.1, 84.7, 83.9, 82.1, 74.8, 73.6, 73.3, 73.3, 73.2, 72.9, 72.8, 72.7, 71.0, 49.5, 45.4, 21.5, 21.3; IR (neat) 3088, 3063, 3031, 2926, 2863, 1793, 1496, 1453, 1367, 1226, 1098, 1074, 1017, 734, 695 cm –1 ; HRMS (ESI) m / z [M + Na] + calcd for C 28 H 30 O 5 SNa 501.1706, found 501.1713; R f = 0.25 (EtOAc/pentane, 10:90). Spectroscopic data was in agreement with literature …”
Section: Methodssupporting
confidence: 89%
“…Crude 22 (1.73 mmol) was dissolved in acetic anhydride (15 mL), and the mixture was stirred at 100 °C for 3 h. The reaction mixture was concentrated in vacuo, and column chromatography (pentane/EtOAc, 90:10 to 80:20) yielded the title compound (0.88 mmol, 0.42 g, 51% over two steps): 1 H NMR (400 MHz, CDCl 3 ) δ 7.41–7.23 (m, 15H), 6.11 (d, J = 4.0 Hz, 1H), 6.02 (d, J = 3.0 Hz, 1H), 4.86–4.50 (m, 6H), 4.30 (dd, J = 5.2, 3.1 Hz, 1H), 4.27–4.12 (m, 2H), 4.07 (dd, J = 6.5, 5.2 Hz, 1H), 3.81 (q, J = 6.4 Hz, 1H), 3.77–3.68 (m, 2H), 3.59–3.39 (m, 3H); 13 C­{ 1 H} NMR (101 MHz, CDCl 3 ) δ 138.4, 138.0, 137.6, 128.6, 128.6, 128.5, 128.5, 128.1, 128.1, 128.0, 128.0, 127.9, 127.9, 127.8, 127.8, 88.9, 86.1, 84.7, 83.9, 82.1, 74.8, 73.6, 73.3, 73.3, 73.2, 72.9, 72.8, 72.7, 71.0, 49.5, 45.4, 21.5, 21.3; IR (neat) 3088, 3063, 3031, 2926, 2863, 1793, 1496, 1453, 1367, 1226, 1098, 1074, 1017, 734, 695 cm –1 ; HRMS (ESI) m / z [M + Na] + calcd for C 28 H 30 O 5 SNa 501.1706, found 501.1713; R f = 0.25 (EtOAc/pentane, 10:90). Spectroscopic data was in agreement with literature …”
Section: Methodssupporting
confidence: 89%
“…Οι Wirshing και Voss το 1999 χρησιμοποίησαν τη D-ξυλόζη ως πρώτη ύλη, για να συνθέσουν ένα ακετυλογλυκοζίτη με τη χαρακτηριστική δομή της αραβινόζης, και στη συνέχεια με την αντίδραση Vorbrüggen συνέδεσαν τη θυμίνη και την ουρακίλη (Σχήμα 2-21). 102 Συνθήκες και αντιδραστήρια: (i) T(TMS)2, TMSOTf, MS, ACN, -18 o C, 2h, 78% (α/β:2/1). Σχήμα 2-21.…”
Section: παλιοτερες συνθεσεις θειονουκλεοζιτωνunclassified
“…Formation of the open-chain dithioacetals from dehydrative glycosylation was a major hurdle and it has been reported in literature. Imbatch's 35 and Voss's 36 research groups reported the synthesis of 4-thio-D-ribofuranose and 4-thio-Dxylofuranose using hydrochloric acid as Brønsted acid and gave dithioacetals as major product in good yields (Figure 1.13). Additionally, Montgomery's research group 37 described the synthesis of 4thio-D-ribofuranose by using SnCl 4 as Lewis acid afforded dithioacetal product in good yield.…”
Section: Dithioacetal Formation From Glycosylationmentioning
confidence: 99%